Development of Random Amplified Polymorphism DNA Markers Linked to Powdery Mildew Resistance Gene in Melon - Budi Setiadi Daryono; Ganies Riza Aristya; Rina Sri Kasiamdari (Indonesian Journal of Biotechnology, 2011)
A random amplified polymorphic DNA (RAPD) marker linked to powdery mildew resistance gene (Pm-I) in melon PI 371795 was reported. However, the RAPD marker has problem in scoring. To detect powdery mildew resistance gene (Pm-I) in melon accurately, the RAPD marker was cloned and sequenced to design sequence characterized amplified region (SCAR) markers. SCAPMAR5 marker derived from pUBC411 primer yielded a single DNA band at 1061 bp. Segregation of SCAPMAR5 marker in bulk of F2 plants demonstrated that the marker was co-segregated with RAPD marker from which the SCAR marker was originated. Moreover, results of SCAR analysis in diverse melons showed SCAPMAR5 primers obtained a single 1061 bp linked to Pm-I in resistant melon PI 371795 and PMAR5. On the other hand, SCAPMAR5 failed to detect Pm-I in susceptible melons. Results of this study revealed that SCAR analysis not only confirmed melons that had been clearly scored for resistance to Pm-I evaluated by RAPD markers, but also clarified the ambiguous resistance results obtained by the RAPD markers.   Key words: Cucumis melo L., Pm-I, RAPD, SCAPMAR5